Mass Loss Controlled Thermal Pretreatment System to Assess the Effects of Pretreatment Temperature on Organic Matter Solubilization and Methane Yield from Food Waste - Yeshanew, Martha M.; Frunzo, Luigi; Lens, Piet N. L.; Pirozzi, Francesco; Esposito, Giovanni (Frontiers in Environmental Science, 2016)
The effects of thermal pretreatment (TP) on the main characteristics of food waste (FW) and its biochemical methane potential (BMP) and distribution of volatile fatty acids (VFAs) under mesophilic condition (35 ⁰C) were investigated. The TP experiments were carried out at 80 °C, 100 °C, 120 °C for 2 hour and 140 °C for 1 hour. The designed TP set-up was able to minimize the organic matter loss during the course of the pretreatments. Soluble organic fractions evaluated in terms of chemical oxygen demand (COD) and soluble protein increased linearly with pretreatment temperature. In contrast, the carbohydrate solubilization was more enhanced (30 % higher solubilization) by the TP at lower temperature (80 °C). A slight increment of soluble phenols was found, particularly for temperatures exceeding 100 °C. Thermally pretreated FW under all conditions exhibited an improved methane yield than the untreated FW, due to the increased organic matter solubilization. The highest cumulative methane yield of 442 (± 8.6) mL/gVSadded, corresponding to a 28.1 % enhancement compared to the untreated FW, was obtained with a TP at 80 °C. No significant variation in the VFAs trends were observed during the BMP tests under all investigated conditions.